The common structure of mentalizing - Ahmad Asgarizadeh; Reihaneh Shoumali; Maryam Tahan (PLoS ONE, 2025)
The primary goal of this research was to investigate the common factor structure of mentalizing by combining items from pre-existing validated tools, cross-validating the resulting structure, and exploring its associations with relevant constructs. Three sequential studies were conducted using community-dwelling samples (total N = 947). Study 1 used exploratory factor analysis on a merged item pool derived from eight measures of mentalizing. Study 2 utilized exploratory structural equation modeling to replicate the extracted structure and investigated its association with psychological dysfunction. Study 3 performed cross-validation of the factor structure and provided criterion-related validity by examining relations with markers of psychopathology and well-being. Factor analyses provided a 10-factor solution that covered distinct facets of mentalizing. Some factors, especially Nonmentalizing-Self and Emotion/Impulse Dysregulation, were strong predictors of dysfunction and psychopathology. Notably, after controlling for positive self-evaluation, individuals reporting greater confidence in understanding others’ minds (Mindreading Self-Concept) showed poorer psychological functioning (β = 0.157, p = .001), in line with theoretical emphasis on humility as a component of genuine mentalizing. The resulting 10-factor structure provides a framework to potentially differentiate between adaptive and maladaptive mentalizing, distinguish its components along the self–other continuum, and discriminate authentic mentalizing processes from subjective assessments of one’s mentalizing capacity.